Analisis kemampuan mahasiswa ilmu perpustakaan angkatan 2019 dalam penelusuran informasi menggunakan search engine google - Sri Nurhayati; Triono Dul Hakim; Hadira Latiar (FPPTI Jawa Tengah, 2022)
This research is entitled analysis of the ability of library science students class of 2019 in searching for information using the Google search engine. The purpose of this study was to find out how Lancang Kuning University's 2019 Library Science Students are Capable of Retrieving Information Using the Google Search Engine. The method used in this research is a quantitative descriptive method. Data collection techniques using observation, questionnaires, interviews, literature studies and documentation. The population and sample in this study amounted to 54 respondents. This study uses data analysis techniques using the Mean formula (calculated average) and the grand mean. The results of this study indicate that the ability of librarian science students class of 2019 at Lancang Kuning University in searching for information using the Google search engine is in the good category with an average value of 3.93 on an interval scale of 3.20-4.20. The author suggests that Library Science Students Class of 2019 at Lancang Kuning University increase their ability to make search statements when accessing information on the Google search engine and evaluate search results so that the information obtained is in accordance with needs.